Evaluation of Addition Tumeric Flour (Curcuma domestica) and Acidifier in Feed on Production Performance of Broiler During Starter Phase - Wahyuni, Nur Maulida; Mustofa, Fatmawati; Sarjana, Teysar Adi; Shihah, Hanna Dzawish; Muryani, Rina; Ma’rifah, Binti; Suprijatna, Edjeng; Sunarti, Dwi; Mahfud , Lutfi Djauhari; Kismiati, Sri; Widodo, Eko; Indrati, Rositawati; Sudjarwo, Edhy (Bantara Journal of Animal Science, 2025)
This study evaluated the addition of turmeric flour (Curcuma domestica) and acidifier in feed on the production Performance of broilers during the starter phase. The materials used in this study were 240 unsexed DOC with an average weight of 40.55±1.69 g/bird. The research method was an experimental trial using a completely randomized design (CRD). There were six treatments and four replications, divided into T0 (commercial feed/basal feed + 0% acidifier + 0% turmeric powder), T1 (basal feed + 0% acidifier + 2.0% turmeric powder), T2 (basal feed + 0.5% acidifier + 1.5% turmeric powder), T3 (basal feed + 1.0% acidifier + 1.0% turmeric powder), T4 (basal feed + 1.5% acidifier + 0.5% turmeric powder), and T5 (basal feed + 2.0% acidifier + 0% turmeric powder). The results showed that the addition of turmeric flour and acidifier in broiler feed during both the starter and finisher phases had a significant effect (p<0.05) on mortality and no significant impact (p>0.05) on feed consumption, weight gain, starter body weight, and FCR. Adding turmeric flour and an acidifier could not increase feed consumption, weight gain, or starter body weight and reduce FCR. However, the addition of turmeric flour and acidifier was able to reduce mortality rates. Further testing related to dosage is needed to achieve the desired results.